2012
DOI: 10.1186/1472-6874-12-41
|View full text |Cite
|
Sign up to set email alerts
|

Comparing health-related quality of life of employed women and housewives: a cross sectional study from southeast Iran

Abstract: BackgroundQuality of life differs for different people in different situations and is related to one's self-satisfaction with life. Considering the role of women in family and social health and the specific cultural characteristics of our province, we aimed to compare the quality of life of employed women with housewives in Zahedan, Iran.MethodsThis cross-sectional study was carried out during 2009–2010 in Zahedan, Iran. The sample consisted of 110 housewives and 110 employed women selected randomly from ten h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 13 publications
3
32
2
3
Order By: Relevance
“…In contrast, a study suggested that employed women are not superior to housewives except for physical dimension (28). In this case, a study suggests that there is no significant difference between employed women and housewives in terms of the quality of life; however, the study recommended that measures be taken to improve housewives' quality of life (29). Irregular menstrual cycles were also a predictor of quality of life in these women, as women with menstrual cycle disorders experienced lower quality of life than women with normal menstrual cycles.…”
Section: Discussionmentioning
confidence: 57%
“…In contrast, a study suggested that employed women are not superior to housewives except for physical dimension (28). In this case, a study suggests that there is no significant difference between employed women and housewives in terms of the quality of life; however, the study recommended that measures be taken to improve housewives' quality of life (29). Irregular menstrual cycles were also a predictor of quality of life in these women, as women with menstrual cycle disorders experienced lower quality of life than women with normal menstrual cycles.…”
Section: Discussionmentioning
confidence: 57%
“…Na análise ajustada não houve diferença estatisticamente significativa na QVRS entre trabalhadoras remuneradas e donas de casa com renda familiar per capita maior ou igual a 3 salários mínimos. Já no estrato intermediário, com renda maior que 1 e menor que 3 salários mínimos, as donas de casa apresentaram menores médias de escores nas escalas de aspectos emocionais (β = -8,6), aspectos sociais (β = -7,4), saúde mental (β = -7,4) e no componente mental (β = -4,4 estudos realizados no Irã comparando a QVRS entre trabalhadoras remuneradas e donas de casa não encontraram diferenças entre estes dois segmentos, após os ajustes por variáveis socioeconômicas 12,13 . Mas, é preciso considerar que as divergências dos resultados podem decorrer de particularidades culturais relacionadas ao papel da mulher na sociedade e ao grau de valorização de sua inserção no processo de trabalho.…”
Section: Resultsunclassified
“…Ainda que existam algumas evidências sobre o benefício do trabalho para a saúde das mulheres, são incipientes e com resultados controversos os estudos que analisaram a qualidade de vida relacionada à saúde (QVRS) 7,8,9,10,11,12,13 . Para a avaliação da QVRS os estudos têm frequentemente utilizado o instrumento The Medical Outcomes Study 36-Item Short-Form (SF-36), que produz medidas do impacto das condições de saúde/doença sobre a funcionalidade do organismo, o bem-estar físico e mental, e o desempenho em atividades sociais 14,15,16 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…[6] According to the results of some studies, the quality of life of employed women is better than nonemployed women. [78]…”
Section: Introductionmentioning
confidence: 99%